Diagnosis of English Students Reading Fluency using Informal Reading Inventory - Eka Nopriani; Fetriani (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The objective of the research was to find out the diagonis of the English Students Reading Fluency using Informal Reading Inventory. The design of this research was descriptive method. The instrument of the research were reading fluency assessment using informal reading inventory and table checklist based on Mc Graw Hill (2017) instruction. The result showed the students include to some reading level they are: Grade 1 : 14 Independently 7 Instructional 2: Frustrational. Grade 2: 11 Independently 5 Instructional 5 Frustrational. Grade 3: 1 Independently 7 Instructional 8 Frustrational. Grade 4: 1 Independently 6 Frustrational Grade 5: 1 Frustrational The highest of independently grade level of students reading fluency in grade 1 (14 students) and grade 2 (11 students) where the students can read the wordlist in one level correctly. The highest of instructional grade level of students reading fluency in grade 1 and grade 3 (7 students) when the students make one mistake in pronounce word in one grade level. The last, frustrational reading level when the students make mistake to pronounce words in two times. It showed that only one students can gone to grade 5. It is suggested the students: The students should practice to reads with correct pronounce more to increase their ability in reading fluency. They can try to often read six level of IRI until can read correct the pronounce of word in grade 6. Key words: reading fluency, Informal Reading Inventory (IRI)